Guds frie nåde, troens frie gensvar: Frelsens betingelser hos N. F. S. Grundtvig og John Wesley - Gregersen, Niels Henrik (Grundtvig-Studier, 2004)
Guds frie nåde, troens frie gensvar: Frelsens betingelser hos N. F. S. Grundtvig og John Wesley [Free Divine Grace andfree Response o f Faith: Conditionalist Motives in N. F. S. Grundtvig and John Wesley] By Niels Henrik Gregersen The essay aims to point out common theological grounds between John Wesley (1703-1791) and N. F. S. Grundtvig (1783-1872). It is argued, first, that Wesley and Grundtvig share the same problem of how to reformulate the Reformation insight in God’s unconditional justification in a context of modernity, in which human freedom is seen as essential also in spiritual matters. It is furthermore argued that Wesley and Grundtvig concur in criticizing the Augustinian-Reformed doctrine of double predestination. Both argue that grace is for all humankind, but grace is not an irresistible force that captivates the human mind. Grace, rather, is a divine self-offering that stimulates the sinner to give a positive response to God’s free offer. Due to his Arminian allegiance, Wesley was an outspoken conditionalist, who explicitly criticized Augustine, Luther, and Calvin. Grundtvig’s critique of Augustine and Luther, by contrast, was mostly of a more indirect nature and couched in his independent use of the Augustinian motifs of grace. The most important difference between Wesley and Grundtvig, however, is that whereas Wesley develops an expanded notion of prevenient grace, Grundtvig expands the traditional notion of creation and imago dei. According to Grundtvig’s doctrine of baptism (central to his so-called Church View), the invitation by Christ to become baptized puts the requirement on the old human being (who is not yet baptized by the Holy Spirit) that he or she must renounce the Devil and embrace the truth of God. Grundtvig’s rich doctrine of imago dei and divine providence can thus be seen as a functional equivalent to Wesley’s doctrine of prevenient grace. Grundtvig, however, never shared Wesley’s view of the possibility of a Christian perfection. Instead, Grundtvig developed a theory of the possibility of a post-mortal conversion (cf. 1 Pet 3). This eschatological vision has the same universal scope as Wesley’s doctrine of prevenient grace, but involves a temporal relaxation as compared with Wesley’s evangelicalism. The common ground between Grundtvig and Wesley casts a new light on the very structure of Grundtvig’s theology. Grundtvig’s “Church View” should not be understood as a precursor to 20th century dialectical theology. Divine action, according to Grundtvig, is certainly primary to human activity, but it is not unilateral. The baptismal covenant between God and the human person involves an “agreement”, or contract, between two parties, God and humanity. God offers His divine grace, but human beings should themselves accept grace in order to be part of salvation. This important motif is reflected in Grundtvig’s doctrinal writings, especially in his doctrine of baptism; however, conditionalist motifs can also be found in his hymns and sermons.